Physician Attitudes About Patient-Facing Information Displays at an Urban Emergency Department - Wilcox, Lauren; Gatewood, Justin; Morris, Dan; Tan, Desney; Horvitz, Eric; Feiner, Steven (Proceedings of AMIA 2010, 2011)
Hospital information systems have primarily been designed to support physicians and administrators, though recent research has explored the value of patient-facing information displays. Electronic systems can be designed to provide tailored information to patients on their health, their care teams, the status of their hospital stays, and their expected care plans. However, this direct delivery of information from database to patient represents a fundamental change to the traditional flow of clinical information. We therefore explore physician attitudes toward a proposed patient-facing display of information abstracted from a hospital EHR, in the context of an urban emergency department. We find that physicians generally support direct delivery of electronic information to patients, and uncover important concerns to consider in the design of patient-facing information systems.